PEDAGOGICAL TECHNOLOGIES FOR MAINTAINING THE PSYCHOPHYSIOLOGICAL HEALTH OF ADOLESCENTS IN ART LESSONS - Терещенко С.В. S.V. (SWorldJournal, 2022)
The content of the publication is actualized with the problem of the preservation of the psychophysiological health of teenagers with the help of art-therapeutic technologies and taking into account the potential of art pedagogy. The interpretation of the